MEDIASI HUBUNGAN INDUSTRIAL OLEH MEDIATOR DINAS KOPERASI DAN TENAGA KERJA KABUPATEN BOYOLALI - Faisal Hernanda Putra; Purwono Sungkowo Raharjo (Jurnal Komunikasi Hukum, 2022)
This study aims to identify and analyze the role of mediators in resolving industrial relations dispute cases and the mediator's obstacles in resolving industrial relations disputes at the Boyolali Regency Cooperative and Manpower Office. This research is a prescriptive normative legal research. This study took place at the Department of Cooperatives and Manpower, Boyolali Regency. The legal material that the author uses is a secondary legal material. The author in this study used a statutory approach with data collection techniques for literature studies and clarification. Furthermore, using data analysis techniques that are deductive in nature. The results of the study show that the role of industrial relations mediators in resolving industrial relations disputes is to facilitate the disputing parties to resolve by deliberation and consensus to reach an agreement, make written recommendations that are submitted to the disputing parties, notify the disputing parties of the importance of registering an agreement. together at the industrial relations court and assist the disputing parties in drafting a collective agreement. Meanwhile, the mediator's obstacle is the difficulty of the entrepreneur to attend the trial held by the mediator, the entrepreneur who is present at the trial is still represented by company employees so that they do not have the authority to decide, the legal counsel of the disputing party is not punctual or deliberately stalls for time in the mediation session, there are still workers / laborers who do not understand the procedure for resolving industrial relations disputes.